Molecular epidemiology of Legionella pneumophila serogroup 1. - van Ketel, R J (1984)
The DNA of patient and environmental isolates of Legionella pneumophila serogroup 1 was analyzed by restriction endonuclease cleavage. The electrophoretic patterns of the DNA digests of isolates from a group of patients with Legionnaires disease acquired in a hospital were indistinguishable from one another and were identical to the DNA pattern of a strain isolated from the hot water supply of the hospital. On the other hand, they were easily differentiated from strains isolated from patients and hot water supplies in other hospitals in the same city. The homogeneity of populations of L. pneumophila serogroup 1 colonizing plumbing systems was also investigated by DNA restriction endonuclease analysis in three hospitals. We distinguished two subtypes in one hospital; the two other hospitals had homogeneous populations. Restriction endonuclease digest analysis of L. pneumophila serogroup 1 DNA enables subtyping and appears to be a useful method for examining the epidemiology of outbreaks of Legionnaires disease.